Forecasting the Equity Premium: Where We Stand Today - Spiegel, Matthew (Review of Financial Studies, 2008)
The Review of Financial Studies has among its missions the facilitation and promotion of a vigorous academic debate across unsettled questions in finance. This issue represents a cross section of views regarding one such debate: Can ourempirical models accurately forecast the equity premium any better than the historical mean? Or, is the forecast our empirical models give us any more accurate than what we would get by simply using the historical mean? The Author 2008. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please email: journals.permissions@oxfordjournals.org., Oxford University Press.